Better clinical outcomes and lower triggering of inflammatory cytokines for allogeneic hematopoietic cell transplant recipients treated in home care versus hospital isolation – the Karolinska experience - Ringdén, Olle; Svahn, Britt-Marie; Moll, Guido; Sadeghi, Behnam (Frontiers in Immunology, 2024)
After allogeneic hematopoietic cell transplantation (Allo-HCT) and conditioning, patients are typically placed in isolated hospital rooms to prevent neutropenic infections. Since 1998, we’ve offered an alternative: home care for patients living within a one to two-hour drive of the hospital. In Sweden this approach includes daily visits by an experienced nurse and daily phone consultations with a unit physician. When necessary, patients receive transfusions, intravenous antibiotics, and total parenteral nutrition at home. Our initial study report compared 36 home care patients with 54 hospital-treated controls. Multivariate analysis found that home care patients were discharged earlier to outpatient clinics, required fewer days of total parenteral nutrition, had less acute graft-versus-host disease (GVHD) grade II-IV, and lower transplantation-related mortality (TRM) and lower costs. Long-term follow-up showed similar chronic GVHD and relapse rates in both groups, with improved survival rates in the home care group. A subsequent comparison of 146 home care patients with hospital-treated controls indicated that home care and longer home stays were associated with lower grades of acute GVHD. Home care was found to be safe and beneficial for children and adolescents. Over two decades, 252 patients received home care post-Allo-HCT without any fatalities at-home. Ten-year outcomes showed a 14% TRM and a 59% survival rate. In 2020, an independent center confirmed the reduced risk of acute GVHD grades II-IV for patients treated in home care. Here, we report for the first time that home care patients also demonstrate a less inflammatory systemic cytokine profile. We found higher levels of IFN-γ, IL-2, IL-5, IL-13, GM-CSF, and G-CSF, but lower VEGF in hospital-treated patients, which may contribute to acute GVHD grades II-IV. In conclusion, home-based treatment following Allo-HCT yields multiple promising clinical outcomes and improved systemic inflammatory markers, which may contribute to less development of life-threatening GVHD.